Notaris dan Penemuan Hukum - Ishaq (Magister Kenotariatan, Universitas Jambi, 2019)
This article describes the concept of a notary public as the law of the legal profession. Notary in the process of legal discovery are problematic, which means the problems posed by the client, where the result is legal but can not be considered as a source of law, because there is no one theory that suggests about the notary is a source of law in finding the law